2018
DOI: 10.1038/s41419-018-1063-2
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacological probe identifies cystathionine β-synthase as a new negative regulator for ferroptosis

Abstract: Cystathionine β-synthase (CBS) is responsible for the first enzymatic reaction in the transsulfuration pathway of sulfur amino acids. The molecular function and mechanism of CBS as well as that of transsulfuration pathway remain ill-defined in cell proliferation and death. In the present study, we designed, synthesized and obtained a bioactive inhibitor CH004 for human CBS, which functions in vitro and in vivo. CH004 inhibits CBS activity, elevated the cellular homocysteine and suppressed the production of hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 56 publications
1
83
0
Order By: Relevance
“…This is accompanied by elevated levels of the cysteine precursor homocysteine in plasma, generating a mouse model for severe homocystinuria [97,98]. Interestingly, a recently developed CBS inhibitor has been identified to induce ferroptosis in different cancer cell lines [99]. Yet, whether any aspect of the Cbs KO phenotype is related to overt induction of ferroptosis is unknown.…”
Section: In Vivo Relevance Of Ferroptosis: Lessons Learned From Knockmentioning
confidence: 99%
“…This is accompanied by elevated levels of the cysteine precursor homocysteine in plasma, generating a mouse model for severe homocystinuria [97,98]. Interestingly, a recently developed CBS inhibitor has been identified to induce ferroptosis in different cancer cell lines [99]. Yet, whether any aspect of the Cbs KO phenotype is related to overt induction of ferroptosis is unknown.…”
Section: In Vivo Relevance Of Ferroptosis: Lessons Learned From Knockmentioning
confidence: 99%
“…Although the pathogenetic role of ferroptosis in ALI induced by seawater drowning is still elusive, its involvement in multiple human diseases has been established. Nowadays, ferroptosis has been recognized as a key mechanism for cell death associated with ischemic organ injury, neurodegeneration and cancer [15][16][17]. Ferroptosis induced by GPX4 inhibition could prevent cancer resistant to chemotherapy [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that seawater exposure changed MLE-12 morphology ( Figure 1A) and decreased cellular viability in time-dependent manner ( Figure 1B). The results of ow cytometry detection of death also showed an increase in the proportion of cell death as the seawater exposure time prolonged ( Figure 1C and D) (17). These results indicate that seawater exposure caused MLE-12 cell damage and death.…”
Section: Seawater Exposure Induced Ferroptosis In Mle-12 Cellsmentioning
confidence: 62%
“…Beijing Cowin Biotech Co., Ltd., China) according to the manufacturer's instructions(17). The assay for lipid ROS was performed by incubating the cells for 1 hour at a nal concentration of 2 μM of BODIPY 581/591 C11 (Invitrogen) at 37 ℃.…”
mentioning
confidence: 99%
See 1 more Smart Citation